SKRINING FITOKIMIA DAN UJI ANTIMIKROBA EKSTRAK KASAR BAWANG BATAK (Allium cinense) TERHADAP BAKTERI Staphylococcus aureus DAN Escherichia coli - Siti Rubiatik; Sartini Sartini; Rosliana Lubis (Universitas Medan Area, 2017)
The purpose of this research is to determine the composition of secondary metabolites of crude extract “bawangbatak” (Allium cinense) and anti-microbial properties of the extract against Staphylococcus aureus and Escherichia coli. This research was conducted in three (3) stage, stage I by the manufacturing of crude extract of garlic bulbs “bawangbatak”, Allium cinense, through maceration method using a solvent n-hexane and methanol. In stage II, screening fitokimia, that is identification of secondary metabolites (alkaloids, flavonoids, terpenoids and steroids) to the crude extract of tuber “bawangbatak”, Allium cinense, and phase III, test bioktifitas crude extract bulb of “bawangbatak” Allium cinense in the form of extracts antimicrobial properties against Staphylococcus aureus and Escherichia coli extract using the concentration variation of 0%, 1%, 5%, 15%, 20%, and 25% and incubation at 370C for 24 hours. The results showed that secondary compounds was dominated by flavonoids, steroids, terpenoid and tannins. While at the test screening phytochemicals extra n-hexane showed no secondary metabolites, test bioktivitas against bacteria have inhibitory at a concentration of 15% with inhibition zone 14 mm in bacteria Escheriachia coli and 10 mm in bacteria Staphylococcus aureus this indicates onion extract of “bawangbatak” has the ability as an anti-microbial.